pengaruh roa dan roe terhadap harga saham perusahaan manufaktur yang terdaftar di bei - armitha, Selly Tria Dinda Armitha (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2021)
The purpose of this study is to examine the effect of ROA and DER on stock prices. The type of this research is quantitative research with a population of financial statements for 2013-2019, manufacturing companies listed on the Indonesia Stock Exchange (IDX). The sample in this research study is only 1 issuer, namely PT. UNILEVER, so that the total data used is 7 data units. Based on the results of the partial t test hypothesis ROA (Retrun on assets) does not affect the stock price at PT. Unilever Indonesia Tbk. Year 2013-2019. While DER (Debt to Equity Ratio) partially has no effect on stock prices at PT. Unilever Indonesia Tbk. Year 2013-2019. Based on the F test results simultaneously ROA (Retrun on assets) and DER (Debt to Equity Ratio) do not affect the stock price at PT. Unilever Indonesia Tbk. Year 2013-2019.